Penerapan model pembelajaran direct instruction dipadukan dengan snowball drilling untuk meningkatkan hasil belajar matematika siswa kelas VI SDN Jejangkit Muara 2 - Rahidatul Laila Agustina; Syarif Hidayatullah (Math Didactic: Jurnal Pendidikan Matematika, 2018)
The purpose of this study was to see how teacher activity increases, student activity and student mathematics learning outcomes in the application of direct instruction learning models combined with snowball drilling. This research is used Classroom Action Research (PTK) and collaborative aproach. The results of data analysis showed an increase teacher activity in learning activities, teacher activity in the first cycle of the first meeting got a score of 24, while the second meeting got a score of 29. and in the second cycle the first meeting got a score of 32 while in the second meeting got a score of 36. Percentage of activity Classical students in the first cycle of the first meeting reached 52% while in the second meeting 62%, and in the second cycle the first meeting reached 76% while at the second meeting reached 89%. Learning outcomes based on the first cycle test I classically reached 65% and then increased in the second cycle reached 90%.